Elevated Serum Uric Acid is Associated With Poor Survival in Advanced HCC Patients and Febuxostat Improves Prognosis in HCC Rats - Wu, Le; Yang, Wenlong; Zhang, Yu; Du, Xiaoyue; Jin, Nan; Chen, Wen; Li, Huangbao; Zhang, Shouhua; Xie, Baogang (Frontiers in Pharmacology, 2021)
Objective: Serum uric acid is associated with tumor progression and hepatocarcinogenesis. Here, we aimed to determine whether serum uric acid is related to the survival time of patients with hepatocellular carcinoma (HCC) and whether the inhibition of uric acid production affects the progression and survival of rats with HCC. Methods: The follow-up data of 288 patients with advanced HCC were analyzed. Ten purine metabolites in serum and liver samples of diethylnitrosamine (DEN)-induced HCC rats were quantitatively determined by an established UPLC-MS/MS method. On this basis, febuxostat, a specific inhibitor of xanthine oxidase (XOD), was used to interfere with HCC rats. Results: The serum uric acid level of HCC patients was significantly negatively correlated with survival days (r = -0.155). The median survival time was 133.5 days in the high uric acid group (>360 μmol/L, n = 80) and 176.0 days in the normal serum uric acid group (<360 μmol/L, n = 208, p=0.0013). The levels of hypoxanthine, guanine, and uric acid; XOD activity; and xanthine dehydrogenase mRNA expression in the serum or liver samples of HCC rats were significantly upregulated compared with those in the control group. After febuxostat intervention in DEN-induced HCC rats, the number of atypical cells and inflammatory cells decreased significantly; the serum alpha fetoprotein level and Fisher’s ratio tended to return to normal; the median survival time increased from 36 days to 96 days (p=0.08). In addition, serum malondialdehyde, superoxide dismutase, and glutathione activity nearly returned to the level of the healthy control group. Conclusions: The elevation of serum uric acid implies a risk of poor survival in advanced HCC patients and Febuxostat can reduce the generation of reactive oxygen species, thereby playing a role in delaying the progression of liver cancer.